HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG MENU SEIMBANG DENGAN STATUS GIZI BALITA 12-59 BULAN - Nugrahanti, Resti; Santosa, Sabar; Setya Arum, Dyah Noviawati (Jurnal Kesehatan Ibu dan Anak, 2015)
Nutrition knowledge of parents affects the choice of children's food, while the food children eat affects nutritional status. Gedongtengen health centers have the highest malnutrition rates in the city of Yogyakarta at 2.66%. Pringgokusumariurban villages are 2.1 5% and 18.26% malnutrition malnutrition. Purpose the examine the relationship between levels of a mother knowing about the balanced menu with the nutritional status of children 12-59. months in neighborhood health center Village Pringgokusuman. Analytic Observational study types with cross-sectional research design, conducted in neighborhood health center Village  Pringgokusuman with 63 sample respondents. Metode sampling used is purposive sampling. This research instrument is the questionnaire and scales infants/toddlers provided neighborhood health center cadres. Data were analyzed using the Kendall Tau test.The result: Mother majority of toddlers have a good knowledge of the balanced menu 55.56% of respondents. Toddlers' majority had good nutritional status as much as 79.37% of respondents. Correlation results in this study so that the p-value 0.033 p-value < 95% confidence level. Conclusions: There is a relationship between the mother's level of knowledge about the balanced menu with children's nutritional status.